2008
DOI: 10.1002/jcla.20225
|View full text |Cite
|
Sign up to set email alerts
|

Association study of CCR5 delta 32 polymorphism among the HLA‐DRB1 Caucasian population in Northern Paraná, Brazil

Abstract: Chemokines are important determinants of early inflammatory response. The CC chemokine receptor 5 (CCR5) delta 32 variant results in a nonfunctional form of the chemokine receptor and has been implicated in a variety of immune-mediated diseases. In the present study, polymerase chain reaction (PCR) for genomic deoxyribonucleic acid (DNA) samples, using specific CCR5 oligonucleotide primers surrounding the breakpoint deletion, detected a 225-basepair (bp) product from the normal CCR5 allele and a 193-bp product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
(38 reference statements)
3
7
2
Order By: Relevance
“…A study performed in Brazil found that 108 ‘Caucasians’ who were HLA-typed as either DRB1*01 or DRB1*04 had a significant probability of carrying the CCR5Δ32 allele [26]. However, we did not find any of the 10 CCR5Δ32/Δ32 CBUs to be HLA-DR*01 .…”
Section: Discussioncontrasting
confidence: 81%
“…A study performed in Brazil found that 108 ‘Caucasians’ who were HLA-typed as either DRB1*01 or DRB1*04 had a significant probability of carrying the CCR5Δ32 allele [26]. However, we did not find any of the 10 CCR5Δ32/Δ32 CBUs to be HLA-DR*01 .…”
Section: Discussioncontrasting
confidence: 81%
“…These results corroborated with studies in different disorders, such as leishmaniasis, breast, laryngeal, thyroid, and brain carcinoma, which also identified no differences in the frequency of these alleles among healthy subjects and patients of Southern Brazilian population [28–30] and worldwide [3133]. …”
Section: Discussionsupporting
confidence: 87%
“…Previous studies in the Brazilian population showed that less than 10% of the investigated individuals carried the heterozygous CCR5Δ-32 genotype 20,21 . The small number of participants included in the present study may have affected the detection of this mutation.…”
Section: Discussionmentioning
confidence: 87%